2011
DOI: 10.1111/j.1464-5491.2011.03257.x
|View full text |Cite
|
Sign up to set email alerts
|

An FTO variant is associated with Type 2 diabetes in South Asian populations after accounting for body mass index and waist circumference

Abstract: Aims-A common variant, rs9939609, in the FTO (fat mass and obesity) gene is associated with adiposity in Europeans, explaining its relationship with diabetes. However, data are inconsistent in South Asians. Our aim was to investigate the association of the FTO rs9939609 variant with obesity, obesity-related traits and Type 2 diabetes in South Asian individuals, and to use metaanalyses to attempt to clarify to what extent BMI influences the association of FTO variants with diabetes in South Asians.Methods-We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 23 publications
6
55
1
Order By: Relevance
“…Thus, with regard to the FTO variant known to be associated with BMI in Europeans, we have recently shown that its association with type 2 diabetes differs between Europeans and South Asians, probably because BMI is a poorer surrogate of adiposity in South Asians [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with regard to the FTO variant known to be associated with BMI in Europeans, we have recently shown that its association with type 2 diabetes differs between Europeans and South Asians, probably because BMI is a poorer surrogate of adiposity in South Asians [14].…”
Section: Introductionmentioning
confidence: 99%
“…The first surge of T2DM GWA identified among others the fat mass and obesity-associated gene (FTO), which is the strongest obesity genetic risk factor reported so far 6,7 . It has been shown to confer susceptibility to T2DM in the presence 8,9 and absence of obesity 10,11 . The most widely studied SNP of the ENPP1, K121Q (rs1044498), has produced conflicting results in relation to T2DM susceptibility [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that Asians have generally lower BMI than Europeans and are more susceptible to T2D probably due to higher visceral obesity [47]. Other studies also reported that the association between FTO loci and T2D remains significant after a BMI adjustment [48,49], but some showed BMI-dependent relation with T2D [23,50]. A meta-analysis from Li et al [26], combining data PRACE POGLĄDOWE of 96,551 Asians from 32 populations, confirmed the association of FTO variance and T2D, which was not abolished after an adjustment of BMI.…”
Section: Fto and Diabetesmentioning
confidence: 88%